Molecular, Clinical and Environmental Toxicology Volume 2: Clinical Toxicology - Luch, Andreas; SpringerLink (Online service) (Basel : Birkhäuser Basel, 2010)
Clinical Toxicology is the second volume of a three-volume set on molecular, clinical and environmental toxicology that offers a comprehensive and in-depth response to the increasing importance and abundance of chemicals of daily life. By providing intriguing insights far down to the molecular level, this three-volume work covers the entire range of modern toxicology with special emphasis on recent developments and achievements. It is written for students and professionals in medicine, science, public health or engineering who are demanding reliable information on toxic or potentially harmful agents and their adverse effects on the human body.
Toxins from bacteria -- Toxicology of mycotoxins -- Phycotoxins: chemistry, mechanisms of action and shellfish poisoning -- Poisonous plants -- Toxic plants: a chemist s perspective -- High-molecular weight protein toxins of marine invertebrates and their elaborate modes of action -- Venomous animals: clinical toxinology -- Mechanistic insights on spider neurotoxins -- Analytical toxicology -- Household chemicals: management of intoxication and antidotes -- Heavy metal poisoning: management of intoxication and antidotes -- Drugs and pharmaceuticals: management of intoxication and antidotes -- Inhalation toxicology -- Biological testing for drugs of abuse -- Drugs of abuse: management of intoxication and antidotes -- Chemical warfare agents -- Biological warfare agents -- Forensic toxicology.
Keywords: Medicine; Toxicology; Biomedicine; Pharmacology/Toxicology.